Current status and future directions for the development of human papillomavirus vaccines - Wang, Rui; Huang, Hongpeng; Yu, Chulin; Li, Xuefeng; Wang, Yang; Xie, Liangzhi (Frontiers in Immunology, 2024)
The development of human papillomavirus (HPV) vaccines has made substantive progress, as represented by the approval of five prophylactic vaccines since 2006. Generally, the deployment of prophylactic HPV vaccines is effective in preventing newly acquired infections and incidences of HPV-related malignancies. However, there is still a long way to go regarding the prevention of all HPV infections and the eradication of established HPV infections, as well as the subsequent progression to cancer. Optimizing prophylactic HPV vaccines by incorporating L1 proteins from more HPV subtypes, exploring adjuvants that reinforce cellular immune responses to eradicate HPV-infected cells, and developing therapeutic HPV vaccines used either alone or in combination with other cancer therapeutic modalities might bring about a new era getting closer to the vision to get rid of HPV infection and related diseases. Herein, we summarize strategies for the development of HPV vaccines, both prophylactic and therapeutic, with an emphasis on the selection of antigens and adjuvants, as well as implications for vaccine efficacy based on preclinical studies and clinical trials. Additionally, we outline current cutting-edge insights on formulation strategies, dosing schedules, and age expansion among HPV vaccine recipients, which might play important roles in addressing barriers to vaccine uptake, such as vaccine hesitancy and vaccine availability.